Hospice in Assisted Living: Promoting Good Quality Care at End of Life - Cartwright, Juliana C. (Oxford University Press, 2009)
Purpose: The purpose of this study was to describe good quality care at the end of life (EOL) for hospice-enrolled residents in assisted living facilities (ALFs). Design and Methods: A qualitative descriptive design was used to obtain detailed descriptions of EOL care provided by ALF medication aides, caregivers, nurses, and hospice nurses in urban and rural settings. A semistructured interview guide facilitated interviews where 38 participants described specific examples of care that “went well.” Results: Findings indicated that the quality and nature of resident–staff and assisted living–hospice staff relationships are critical in promoting good care at EOL for ALF residents on hospice. Length of the resident's stay in the facility and how well staff knew the resident were associated with the quality of the resident–staff relationship. Respectful collaboration, clear communication, use of complementary knowledge and skills of staff, and shared expectations about the care were associated with positive staff relationships. Also important was ALF administrator support for residents’ dying in place with hospice services. Implications: ALFs choosing to support residents dying in their facility will benefit from developing systems of care that promote resident–staff relationships and optimize communication and collaboration among ALF care providers and with hospice staff. Hospice programs should design their services to support ALF staff as well as patients and families. Now needed are development and testing of models of care by hospice and ALF to support the care needs of ALF residents at EOL.